Evidence for Fluctuating Wind in Shaping an Ancient Martian Dune Field: The Stimson Formation at the Greenheugh Pediment, Gale Crater. Issue 9 (23rd September 2022) - Banham, Steven G.; Gupta, Sanjeev; Rubin, David M.; Bedford, Candice C.; Edgar, Lauren A.; Bryk, Alex B.; Dietrich, William E.; Fedo, Christopher M.; Williams, Rebecca M.; Caravaca, Gwénaël; Barnes, Robert; Paar, Gerhard; et al.
Abstract: Temporal fluctuations of wind strength and direction can influence aeolian bedform morphology and orientation, which can be encoded into the architecture of aeolian deposits. These strata represent a direct record of atmospheric processes and can be used to understand ancient Martian atmospheric processes as well as those on Earth. The strata can: give insight to ancient atmospheric circulation, how the atmosphere evolved in response to global changes in habitability, and how ancient processes differ from modern processes. The Stimson formation at the Greenheugh pediment (Gale crater) records evidence of fluctuating wind across multiple temporal scales. The strata can be subdivided into three intervals–Gleann Beag, Ladder, and Edinburgh intervals. Internally, the intervals record changes of dune morphology and orientation, correlatable to wind fluctuations at multiple temporal scales. The basal Gleann Beag interval comprises compound cross‐strata, deposited by oblique compound dunes. These dunes record a bimodal wind regime, resulting in net sediment transport toward the north. The Ladder interval records a reversal of sediment transport to the south, where straight‐crested simple‐dunes shaped by a seasonally variable winds formed. Finally, the Edinburgh interval records sediment transport to the west, where a unimodal wind formed sinuous‐crested simple dunes. These observations demonstrate active and variable atmospheric circulation in Gale crater during the accumulation of the Stimson dune field, at multiple temporal scales from seasonally driven winds to much longer time‐frames, during the Hesperian. These observations can be used to further understand ancient atmospheric conditions and processes, at a high temporal resolution on Mars. Plain Language Summary: The direction and strength of the wind varies, but typically follows predictable patterns over a variety of time‐scales ranging from the course of a day or a year through to decades or millennia. Within a dune field, these patterns of air flow control the shape, size and orientation of aeolian landforms‐such as dunes and ripples–and in‐turn be recorded in the rock record, where sediment accumulates over time. These deposits form a record of ancient atmospheric processes, and can be found on Mars, as well as Earth. On Mars, within the Stimson sandstone, evidence for short‐ and long‐term wind trends are identified in these strata deposited by ancient dunes. This partial record–resulting from episodic erosion and deposition characteristic of dune migration–indicates dunes were shaped by seasonal and longer‐term sediment transport processes, and that the shape of dunes, and their orientation changed in response long‐term changes in wind direction. These changing winds give us insight to the prevailing climate controlling the wind within Gale crater during the Hesperian period and can be used to constrain climate models and gain insight to habitability at that time. Key Points: The Greenheugh pediment capping unit is part of the Stimson formation, containing architectural elements consistent with aeolian processes Here, the formation is subdivided into three intervals based on sedimentary architecture: Gleann Beag, Ladder and Edinburgh intervals The preserved architecture is a product of fluctuating wind at multiple temporal scales, recording seasonal through to millennial cycles